Comparison Between Ferguson’s Technique and Mitchelle Bank Technique for Inguinal Herniotomy in Children - rehman, shafqat; Ahmed, Iftikhar; Awan, Safdar Hussain; Anwar, Zahid; Saleem, Muddasir; Afzal, Tamoor (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the safety of the Mitchelle bank technique for herniotomy in children by comparing its recurrence rate with conventional Ferguson’s technique. Study Design: Quasi-experimental study. Place and Duration of Study: Paediatric Surgery Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Sep 2019. Methodology: Children below the age of 6 years coming to Paediatric Surgery Outpatient Department with inguinal hernia were included in the study. The patients were divided into two groups. Group-I underwent herniotomy by Mitchelle bank technique (MBT-group) while Group-II by Ferguson’s technique (FT-group). The demographic characteristics of the studied population, operative time, and intra-operative and post-operative complications were recorded. Results: The mean age of the patients was 25.94 ± 17.06 months in Ferguson’s technique-group and 24.76 ± 16.63 months in the Mitchelle bank technique-group. The mean operative time was less in the Mitchelle bank technique-group (13.17 ± 1.47 minutes) as compared to Ferguson’s technique-group (16.23 ± 1.51 minutes) (p<0.05). Early complications such as hydrocele, seroma and hematoma were seen in 5 (2.3%), 6 (2.6%) and 3 (1.3%) cases in Ferguson’s technique-group, and 15 (6.9%), 8 (3.7%), and 9 (4.1%) cases in the Mitchelle bank technique group, respectively. Late complications such as orchitis, testicular atrophy, and recurrence were seen in 5 (2.3%), 6 (2.6%), 2 (0.9%) in Ferguson’s technique group, and 6 (2.6%), 4 (1.8%), and 3 (1.3%) in the Mitchelle bank technique group (p>0.05). Conclusion: Mitchelle bank technique is safe for herniotomy in children with less operative time and no increase in...